How to Read The Bible (Not Only) in Times of Pandemic - Yépez Barrientos CM, Mario (2020)
In this article, I want to propose some warnings about a proper reading of the biblical text because some readers persist in the fundamentalist interpretation, even some Catholics readers - and this interpretations have been strong in pandemic times - who notoriously distorts the true meaning of what we affirm when we say that the Bible is the Word of God, moving away from a coherent interpretation and that it can help the theological debate today too. If we want to achieve this, in the first place, I will try to place the problem of the approach to biblical texts of a fundamentalist nature - and it could be very dangerous and tempting -; in the second place, I will present some preliminary guidelines to adequately approach the biblical texts according to the orientations of the Magisterium of the Church and the advances in the studies of biblical sciences; and finally, I will offer you a conclusive opinion about the importance of the texts of the Bible in terms of your religious perspective for the daily reading in the life of believers and even for who wish to know